2009
DOI: 10.1111/j.1472-765x.2009.02710.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and phylogeny of eukaryotic 18S rDNA phylotypes detected in chlorinated finished drinking water samples from three Parisian surface water treatment plants

Abstract: Aims:  We performed a preliminary assessment of the eukaryotic 18S rDNA diversity present in finished drinking water samples from three different surface water treatment plants supplying water to the city of Paris (France). Methods and Results:  A molecular analysis was performed on a sample from each site based on sequencing of PCR amplified and cloned 18S ribosomal RNA genes. Overall, the 18S rDNA sequences combined from all samples could be affiliated to the Amoebozoa (20·8% of the phylotypes), Ciliophora (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…To aid in comparing read distributions between the environments we chose six clades for illustrative purposes with the earliest diverging called groups '1' and '2', internal clades called groups '3' and '4', and the last diverging clades called groups '5' and '6' (Fig. In all three environments group 6 was the most consistently abundant (Aquifer -24% of reads, marine -30%, freshwater -25%) containing reference sequences from freshwater lakes/ponds (Lefranc et al, 2005;Šlapeta et al, 2005;Jones et al, 2011b), a drinking water treatment system (Poitelon et al, 2009), a landfill leachate contaminated aquifer (Brad et al, 2008), and an acidic metal rich stream (Amaral Zettler et al, 2002). In all three environments group 6 was the most consistently abundant (Aquifer -24% of reads, marine -30%, freshwater -25%) containing reference sequences from freshwater lakes/ponds (Lefranc et al, 2005;Šlapeta et al, 2005;Jones et al, 2011b), a drinking water treatment system (Poitelon et al, 2009), a landfill leachate contaminated aquifer (Brad et al, 2008), and an acidic metal rich stream (Amaral Zettler et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To aid in comparing read distributions between the environments we chose six clades for illustrative purposes with the earliest diverging called groups '1' and '2', internal clades called groups '3' and '4', and the last diverging clades called groups '5' and '6' (Fig. In all three environments group 6 was the most consistently abundant (Aquifer -24% of reads, marine -30%, freshwater -25%) containing reference sequences from freshwater lakes/ponds (Lefranc et al, 2005;Šlapeta et al, 2005;Jones et al, 2011b), a drinking water treatment system (Poitelon et al, 2009), a landfill leachate contaminated aquifer (Brad et al, 2008), and an acidic metal rich stream (Amaral Zettler et al, 2002). In all three environments group 6 was the most consistently abundant (Aquifer -24% of reads, marine -30%, freshwater -25%) containing reference sequences from freshwater lakes/ponds (Lefranc et al, 2005;Šlapeta et al, 2005;Jones et al, 2011b), a drinking water treatment system (Poitelon et al, 2009), a landfill leachate contaminated aquifer (Brad et al, 2008), and an acidic metal rich stream (Amaral Zettler et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Recently named 'Cryptomycota' (Jones et al, 2011a) members have appeared in molecular surveys of soil (Moon-van der Staay et al, 2006;Lesaulnier et al, 2008), lakes and rivers (Amaral Zettler et al, 2002;Lefranc et al, 2005;Lefèvre et al, 2007), oceans (Takishita et al, 2005), groundwater (Luo et al, 2005;Brad et al, 2008), and a drinking water treatment system (Poitelon et al, 2009), and are typically identified simply as an 'unclassified fungus'. Yet somehow, one massive group representing perhaps half or more of all fungi has managed to escape our grasp until very recently.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature can affect the identity of the FLP in drinking water supplies, but in both regions, clones clustered within Amoebozoa, Cercozoa, Choanozoa, Ciliophora, and Stramenopiles (Fig. 3) (33,50,51). However, sequences related to Euglenozoa and Myzozoa were observed only in the temperate region, although certain euglenozoan types have been found in a volcanic area at a temperature above 30°C (44).…”
Section: Discussionmentioning
confidence: 99%
“…Most information on community composition and abundance of FLP in freshwater environments has been obtained by using cultivation methods and microscopy. Recently, however, the presence and identities of such organisms in drinking water supplies in temperate regions have been studied by using molecular methods for detection and identification (33,51). In two groundwater supplies in the Netherlands a total of 127 operational taxonomic units (OTUs) of FLP were identified based on their 18S rRNA gene sequences.…”
mentioning
confidence: 99%
“…DNA was precipitated with ethanol and dissolved in 0.5 mL water. AmpliWcation of the 18S ribosomal RNA (rRNA) gene used the following primers: 18S-4F (CTGGTTGATYCTGCCAGT) and 18S-1787R (CAGGTTCACCTACRG) [21]. Polymerase chain reactions (PCRs) were done with rTaq (Amersham) and included 50 ng template and 10 ng of each primer.…”
Section: Biomass Extraction and Transesteriwcation Of Fatty Acidsmentioning
confidence: 99%